Attitude and practice on human papilloma virus infection and vaccination among students from secondary occupational health school: a cross-sectional study. Issue 11 (2nd November 2021) - Wang, Xin; Du, Taifeng; Shi, Xiaoling; Wu, Kusheng
ABSTRACT: Cervical cancer (CC) is reported as the second-most common female cancer worldwide, of which 99% is caused by persistent human papillomavirus (HPV) infection. HPV vaccine protects against HPV infection and most cases of CC, which has only been introduced for a short time in mainland China. This study aimed to evaluate the attitude and practice related to HPV infection and vaccination among students at secondary occupational health school (SOHS) in China. We conducted a cross-sectional study in Southern China where data of 2248 participants were collected through questionnaires to estimate attitude and practice of students. Only 4.1% believed they were easily infected by HPV, 38.2% were willing to receive HPV vaccine and 30.8% intended to do regular screening of HPV infection in the future. Students in the second grade (OR = 1.51, 95%CI [1.25, 1.81]) and third grade (OR = 3.99, 95%CI [2.53, 6.27]) were more willing to take HPV vaccine compared to students in the first grade. Among the non-vaccinated participants, the most frequent reason for not receiving HPV vaccine was insufficient knowledge about HPV (91.1%). Characteristics of higher grade, personal education before enrollment and academic performance, medical specialty, history of sex experience and HPV vaccine and family history of other cancers were associated with higher attitude scores ( p < .05). Considering the increasing prevalence of HPV infection and the need of improvement in attitude and practice toward HPV, more education about HPV infection and vaccination should be incorporated into school curriculum.